Fertility of sod-podzolic soils and productivity of perennial grasses in long-term use of mineral fertilizers at the background of liming - N. V. Bulatova; N. V. Regorchuk (Аграрная наука Евро-Северо-Востока, 2017)
The effect of application of mineral fertilizers at the background of long-term (20 years) aftereffect of liming on agrochemical properties of sod-podzolic middle-loamy soil and yield of the clover-timothy mixture was studied in the field stationary experiment. It was established that at single application of dolomite powder in a dose of 1 unit of hydrolytic acidity (h.a.) the soil acidity is supported on level of medium acidity - рНkcl 4.6...4.7, in a dose of 2 h.a. - on level from slightly acidic upto next to neutral - рНkcl 5.5...5.6. Growing up of perennial grasses for 5 years contributed to the preservation of humus content in the soil at the level of 1.56 to 1.74% at the initial 1.5%. The degree of soil saturation with bases (V) at the background of lime aftereffect in dose of 1 h.a. made up 69.74%, which indicates a weak need of soil in the re-liming. At the background of aftereffect of lime input in a dose of 2 h.a. it is not required ameriorant inputting (V = 81.83%). Annual application of mineral fertilizers contributed to the accumulation of mobile phosphorus in the soil to high and very high level (173.281 mg/kg), and exchangeable potassium to the medium level (115.132 mg/kg). The degree of phosphorus mobility increased with increasing doses of mineral fertilizers, the maximum values (0.30.0.35 mg/l) were obtained on limed backgrounds. The aftereffect of lime had no effect on potassium mobility, which one was determined by the dose of fertilizers applied - 5.7...6.6 mg/l (N30P45K45), 9.0.13.9 mg/l (N60P75K75). Plants better used nutritions from fertilizer when they are inputted at the background of lime aftereffect: phosphorus - up to 27.34%, potassium - up to 76.96%. Utilization of phosphorus from soil was 25.34%, potassium - 32.40%. Inputting of N60P75K75 at the background of dolomite aftereffect at a dose of 2 h.a. provided the highest yield of dry mass of perennial grasses - 4.7 t/ha. When mineral fertilizers, independently on lime action the balance of phosphorus was positive, of potassium - negative. Intensity of balance was, respectively, 157.259% and 61.89%.